Manufacturing processes for textile and fashion design professionals - Thompson, Rob (Designer); Thompson, Martin (Photographer) (New York : Thames & Hudson, 2014)
To be truly prized and employable, textile and fashion designers have to be aware of, and knowledgeable about, a wide range of processes to enable their designs to be manufactured effectively, often thousands of miles from their design studio. This much-needed new reference is the only encyclopedic guide to manufacturing processes and materials that is truly relevant for textile and fashion designers. It is organized into five main parts: fiber and yarn technology; textile technology; construction technology; life cycle strategies; and materials appendix. This book is a complete overview of the life cycle of textile and fashion manufacturing, from the spinning of yarn to recycling. All the processes feature detailed step-by-step case studies showing the process in manufacture at a leading international supplier. The appendix features essential knowledge on over sixty natural and synthetic materials. With around 1,400 specially commissioned photographs and technical illustrations, this is the indispensable, reliable, convenient, and highly accessible practical reference for all textile and fashion designers.--
boek